Without proper research funding, how can medical education be evidence based?. (26th June 2015) - Archer, Julian; McManus, Chris; Woolf, Katherine; Monrouxe, Lynn; Illing, Jan; Bullock, Alison; Roberts, Trudie
Abstract : We can no longer leave research into medical education to chance